An Utilization Of Social Capital In Empowering BUMDes Buduma In Buluh Duri Village - Farid Aulia; Agustrisno, Agustrisno (Jurnal Scientia, 2024)
The management of ecotourism-based rafting in Buluh Duri Village through empowerment of BUMDes administrators is still constrained in various aspects. These aspects include: the low ability of BUMDes administrators to overcome the less than optimal BUMDes partnership, the low knowledge of BUMDes administrators about the use of social capital in managing tourist areas as an effort to improve the village community's economy, the low empowerment of village officials in organizing partnerships and collective business management based on social capital, including: services that prioritize comfort, hospitality, cleanliness, various halal foods with delicious and affordable flavors, the availability of adequate infrastructure, maintaining environmental cleanliness from organic and non-organic waste. This condition needs to be followed up by carrying out a community service program. This activity is carried out to empower BUMDes administrators and the community in providing the use of social capital. The purpose of this economic and social service activity is to help reduce partnerships that have experienced problems, increase the knowledge of BUMDes administrators as a driving force regarding the development of tourist areas in managing them as an effort to improve the village community's economy, increase the empowerment of village officials in organizing partnerships and collective business management based on social capital. To achieve these goals, the methods used in this activity are: Socialization and Training on Utilization of Social Capital, Participatory Organization, Monitoring and Evaluation. The results of this economic and social service are that the partner group (BUMDes BUDUMA administrators) are able to become community drivers in utilizing social capital in developing BUMDes BUDUMA sustainably through the development of BUMDes that can improve community welfare.